Potentially preventable complications of urinary tract infections, pressure areas, pneumonia, and delirium in hospitalised dementia patients: retrospective cohort study. Issue 6 (1st June 2013) - Bail, Kasia; Berry, Helen; Grealish, Laurie; Draper, Brian; Karmel, Rosemary; Gibson, Diane; Peut, Ann
Abstract : Objectives: To identify rates of potentially preventable complications for dementia patients compared with non-dementia patients. Design: Retrospective cohort design using hospital discharge data for dementia patients, case matched on sex, age, comorbidity and surgical status on a 1 : 4 ratio to non-dementia patients. Setting: Public hospital discharge data from the state of New South Wales, Australia for 2006/2007. Participants: 426 276 overnight hospital episodes for patients aged 50 and above (census sample). Main outcome measures: Rates of preventable complications, with episode-level risk adjustment for 12 complications that are known to be sensitive to nursing care. Results: Controlling for age and comorbidities, surgical dementia patients had higher rates than non-dementia patients in seven of the 12 complications: urinary tract infections, pressure ulcers, delirium, pneumonia, physiological and metabolic derangement (all at p<0.0001), sepsis and failure to rescue (at p<0.05). Medical dementia patients also had higher rates of these complications than did non-dementia patients. The highest rates and highest relative risk for dementia patients compared with non-dementia patients, in both medical and surgical populations, were found in four common complications: urinary tract infections, pressure areas, pneumonia and delirium. Conclusions: Compared with non-dementia patients, hospitalised dementia patients have higher rates of potentially preventable complications that might be responsive to nursing interventions.